L’activité informatique et l’accessibilité économique - Maxime Schirrer (Netcom)
Through the study of three territories of the Parisian metropolis, in relation to a political, economic and territorial approach, our analysis results in drawing a picture on the tendencies of localization of the computing activity which take place in the urban surface most dynamic of France. Heart of the Parisian metropolis with two territories in metropolitan fringe, Yvelines and the Seine-et-Marne, new accessibilities as regards digital economy at the base of a functional reorganization of metropolitan space? Do they contribute to a territorial recombining of economic spaces of the area ? Does the technical paradigm then induce a new relation with the centrality?